A Nurse Leadership Project to Improve Health Literacy on a Maternal‐Infant Unit. Issue 5 (21st August 2015) - Stikes, Reetta; Arterberry, Katheryn; Logsdon, M. Cynthia
ABSTRACT Objective To describe how participation in the Sigma Theta Tau International Maternal‐Child Health Nurse Leadership Academy positioned the authors to lead an interdisciplinary team through implementation and evaluation of a change project related to patient education based upon national health literacy standards. The project goal was to improve patient satisfaction with nurse communication and preparation for hospital discharge. Design Quality improvement. Setting/Participants Mother/‐baby unit of an academic medical center serving a high percentage of patients of a minority population and underserved clients. Intervention The five‐ step intervention included (a) review of current health literacy standards, (b) formation of an infrastructure for development and evaluation of existing patient education materials, (c) assessment of patient education materials currently in use, (d) assessment of literacy level and learning styles of new mothers, and (e) provision of continuing education to increase knowledge of nurses as patient teachers and of health literacy. Measurement Mean scores of Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) in the domains of patient satisfaction with nurse communication and discharge information were used to measure patient satisfaction with health communication. Results Patient satisfaction with nurse communication increased from 75.9% to 84.6%. Satisfaction with discharge information increased from 84.6% to 98.6%. Conclusion The leadership academy successfully positioned the authors to guide an interdisciplinary team through development of a process to meet the education and communication needs of patients and improve their health literacy. As a result, a positive effect was noted on patient satisfaction with health communication.